Profile of neurological disorders in an adult neurology clinic in Kumasi, Ghana - Fred Stephen Sarfo; John Akassi; Elizabeth Badu; Aham Okorozo; Bruce Ovbiagele; Albert Akpalu (eNeurologicalSci, 2016)
Background: Although the burden of neurological disorders is highest among populations in developing countries there is a dearth of data on the clinical spectrum of these disorders. Objective: To profile the frequency of neurologic disorders and basic demographic data in an adult neurology out-patient service commissioned in 2011 in Kumasi, Ghana. Methods: The study was conducted at the neurology clinic of the Komfo Anokye Teaching Hospital in Kumasi, Ghana. Over a three year period, all medical records of patients enrolled at the out-patient neurology clinic was reviewed by a neurologist and neurological diagnoses classified according to ICD-10. Results: 1812 adults enrolled for care in the neurology out-patient service between 2011 and 2013. This comprised of 882 males and 930 females (male: female ratio of 1.0: 1.1) with an overall median age of 54 (IQR, 39–69) years. The commonest primary neurological disorders seen were strokes, epilepsy and seizure disorders, and movement disorders at frequencies of 57.1%, 19.8%, and 8.2% respectively. Conclusions: Cerebrovascular diseases, epilepsy and movement disorders were among the commonest neurological disorders and the major contributors to neurologic morbidity among Ghanaians in an urban neurology clinic.